2010
DOI: 10.1016/j.joca.2010.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic loading enhances integrative meniscal repair in the presence of interleukin-1

Abstract: Objective Meniscal tears are a common knee injury and increased levels of interleukin-1 (IL-1) have been measured in injured and degenerated joints. Studies have shown that IL-1 decreases the shear strength, cell accumulation, and tissue formation in meniscal repair interfaces. While mechanical stress and IL-1 modulate meniscal biosynthesis and degradation, the effects of dynamic loading on meniscal repair are unknown. The purpose of this study was to determine the effects of mechanical compression on meniscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 63 publications
4
65
0
Order By: Relevance
“…Importantly, the reduced ability of OP1 to stimulate extracellular matrix gene expression and to reduce MMP expression in meniscus cells obtained from end-stage OA knee joints suggests that factors associated with OA inhibit the response to OP1. We found evidence that these could include IL1α, IL1β, and FnF which have been found to be present in torn meniscus and/or OA joint fluid [26, 27]. We also confirmed previous work [13] that unlike the meniscus, OA chondrocytes do not appear to become unresponsive to OP1 suggesting differences in the regulation of OP1 signaling between these two joint tissues.…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, the reduced ability of OP1 to stimulate extracellular matrix gene expression and to reduce MMP expression in meniscus cells obtained from end-stage OA knee joints suggests that factors associated with OA inhibit the response to OP1. We found evidence that these could include IL1α, IL1β, and FnF which have been found to be present in torn meniscus and/or OA joint fluid [26, 27]. We also confirmed previous work [13] that unlike the meniscus, OA chondrocytes do not appear to become unresponsive to OP1 suggesting differences in the regulation of OP1 signaling between these two joint tissues.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, a previous canine ACL transection study (Adams et al, 1983) documented initial decreases in meniscal GAG at 1 week post injury with levels returning to normal or above normal after 15–18 months. This initial decrease in GAG could be due to an inflammatory response, as numerous studies (Lemke et al, 2010; McNulty et al, 2010) have demonstrated GAG degradation under inflammatory conditions. We were limited in our assessment of GAG changes, as they may be temporal and this study is presenting results from a single time point of 12 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…Dynamic compressive loading was performed as previously described (60). Briefly, a closed-loop displacement controlled bioreactor with 24 individual polyacetal pistons connected to a linear stage driven by a stepper motor was used to deliver a 10% peak-to-peak sinusoidal strain (7% offset) at 1 Hz for 3 h/d.…”
Section: +2mentioning
confidence: 99%